What Do You Mean by Trust? Establishing Shared Meaning in Interdisciplinary Design for Assistive Technology - Schwaninger, Isabel; Güldenpfennig, Florian; Weiss, Astrid; Fitzpatrick, Geraldine (International journal of social robotics, 2021)
The topic of trust has attracted increasing interest within HRI research, and is particularly relevant in the context of social robots and their assistance of older people at home. To make this abstract concept of trust more tangible for developers of robotic technologies and to connect it with older people’s living spaces and their daily practices, we propose a light-weight method drawing on elicitation cards to be used at early stages of participatory design. The cards were designed to serve as a guide for qualitative interviews at ideation phases. This was accomplished by using the cards connected to the living spaces of the participants, their daily practices, and ‘provocative’ questions to structure conversations. We developed the method with 10 inexperienced interviewers who conducted 10 qualitative interviews on the topic of trust without cards, and who tested the cards with 10 older adults. Our findings indicate that the method served as a powerful facilitator of conversations around the topic of trust and enabled interviewers to engage with everyday practices of older adults; it also facilitated a more active role for older adults during the conversations. As indicators of findings that can come from the cards, salient trust-related themes that emerged from the analysis of card usage were the desire for control, companionship, privacy, understandability, and location-specific requirements with regards to trust.